Changes to SNAP-authorized retailer stocking requirements and the supply of foods and beverages in low-income communities in seven U.S. states. Issue 5 (30th September 2019) - Powell, Lisa M; Singleton, Chelsea R; Li, Yu; Anderson Steeves, Elizabeth; Castro, Iana A; Grigsby-Toussaint, Diana; Haynes-Maslow, Lindsey; Houghtaling, Bailey; Laska, Melissa N; Leone, Lucia A; Seguin, Rebecca; Uslan, Daniella
Abstract : Less than one-half of small food stores audited in low-income communities met the USDA's 2016 proposed expansion of the Supplemental Nutrition Assistance Program-authorized retailer stocking requirements. Abstract: Low-income communities often lack access to supermarkets and healthy foods. Enhanced stocking requirements for staple foods for Supplemental Nutrition Assistance Program (SNAP)-authorized retailers may increase availability of healthy foods in smaller stores which are prevalent in low-income areas. This study aimed to evaluate the extent that small food stores located in low-income areas met the U.S. Department of Agriculture's 2016 final rule on SNAP-authorized retailer stocking requirements, which increased the minimum number of required staple food varieties from three to seven for each staple food category, required a depth of stock of three units of each variety, and increased the required number of categories with perishables from two to three. A multisite research project was conducted in 2017. Nine research teams located in seven U.S. states audited the availability of perishable and nonperishable staple foods and beverages in 351 small food stores in low-income areas. Analyses determined the extent to which stores met all or part of the stocking requirements and tested differences by store type. 30.2% of stores met all of the 2016 final rule requirements; 86.3% met the requirements for fruits and vegetables, whereas only 30.5% met requirements for dairy. 53.1% of non-chain small grocery stores met all requirements compared to 17.1% of convenience stores ( p < .0001). Less than one half of the food stores audited met the U.S. Department of Agriculture's 2016 final rule that would expand SNAP-authorized retailer stocking requirements suggesting that, if implemented, the rule may generate increased offerings of staple foods in small stores in low-income areas.